2021
DOI: 10.2478/fon-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the patient's success in facing post-stroke urinary incontinence: the patient's perspective

Abstract: Objective Post-stroke urinary incontinence (UI) is one of the sequelae of stroke. This situation affects all aspects of the patient's life – physically, psychologically, socially, and spiritually. This study aimed to investigate the experience of patients’ success in facing a post-stroke UI. Methods A qualitative study using the Rapid Assessment Procedure (RAP) approach was used in this study. Informants were selected using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The active participation of the patient can improve the patient's functional ability (Heltty, 2022). Active participation can be achieved by cultivating enthusiasm within the patient to carry out activities (Heltty, 2021). This enthusiasm is part of resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The active participation of the patient can improve the patient's functional ability (Heltty, 2022). Active participation can be achieved by cultivating enthusiasm within the patient to carry out activities (Heltty, 2021). This enthusiasm is part of resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to family, attention from peers who also experienced the same disease can help reduce feelings of isolation and fear, where peer interaction can be done by sharing experiences and providing information about the health services they need [ 14 ]. The results of our previous qualitative research found that the presence of peers in the patient care process made the informants (patients) feel happy and not alone in dealing with their illness, making the informants became more eager to recover [ 16 ]. This study aimed to investigate the relationship between patient, family, and peer involvement in nursing care to improve the functional independence of post-stroke UI patients.…”
Section: Introductionmentioning
confidence: 99%